Escolas sustentáveis : três experiências no município de São Leopoldo - RS - Grohe, Sandra Lilian Silveira (2015)
Over recent years, the public policy proposition for sustainable schools has been establishing itself in Brazil, in order to transform elementary school institutions into sustainable education places, through encouraging sustainability education.The main purpose of this research consists in observe how the propositon for the sustainable school is constituting itself as a public policy in Brazil. This research also aims at understanding how the schools will be able to transform themselves into sustainable education places indeed and investigate if this proposition is capable of providing local movements of environmentalization.and ecologically correct attitudes.For this purpose, I spent those last two years as a teacher and reseacher searching for documents, I interviewed some people and I observed three schools from Sao Leopoldo, a metropolitan city near to Porto Alegre in Rio Grande do Sul,southern Brazil, in an attempt to understand and describe how the policy proposition for sustainable schools happens. I noticed that the environmentalization process is one of the inherent purposes of the policy for sustainable school, that helps to create sustainable educator places. as well as, it is a proposition that gives priority to the horizontal dialogue and encourages educational processes sensitizers. The children and Youth nacional conference on the Environment and the Committee for the Environment and Quality of life were identified as link between the proposition and the school and also bringing news partners.The proposition for the Sustainable School brings the Curriculum, the management and the physical spaceas shafts articulators, however was identified that without commited and available peoples these axles do not articulate.The training process was verified as essential to the strengthening of the policy, however this process needs to be present in all states of Brazil. The policy proposition for Sustainable Schools needs to be systemic to get succeed, strengthened by training process, legislation, conferences, committees, commited and availables teachers and, thereby provoker of local changes and, therefore, global.